1979
DOI: 10.1021/jm00195a026
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomotropic agents. 1. Synthesis and cytotoxic action of lysosomotropic detergents

Abstract: Amines whose pK values lie between about 5 and 9 are lysosomotropic because lysosomes are acidic intracellular compartments. If such amines bear long hydrophobic chains, they become detergents upon protonation inside the lysosomes, rupturing the lysosomal membrane and killing the cell. Six types of lysosomotropic amines have been prepared that all behave in the expected manner. They are cytotoxic to all lysosome-bearing cells but not red blood cells, which lack lysosomes. Their mode of action, the effect of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
105
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 6 publications
2
105
0
Order By: Relevance
“…1A). 37 Furthermore, our recent in vitro studies confirm that siramesine is an amphiphilic compound that partitions into the air/water interface and binds to acidic phospholipids with high affinity thereafter penetrating into the hydrocarbon core of the membrane (Parry MJ, Alakoskela J-MI, Jäättelä M, Mahalka A, Kinnunen PKJ, unpublished data). Finally, the characteristics of siramesine-induced cell death, e.g., an early lysosome damage occurring prior to cell rounding and death, dependence on cysteine cathepsin activity and cell density as well as a highly sigmoidal dose-response curve, 10 closely resemble those of other lysosomotropic detergents.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…1A). 37 Furthermore, our recent in vitro studies confirm that siramesine is an amphiphilic compound that partitions into the air/water interface and binds to acidic phospholipids with high affinity thereafter penetrating into the hydrocarbon core of the membrane (Parry MJ, Alakoskela J-MI, Jäättelä M, Mahalka A, Kinnunen PKJ, unpublished data). Finally, the characteristics of siramesine-induced cell death, e.g., an early lysosome damage occurring prior to cell rounding and death, dependence on cysteine cathepsin activity and cell density as well as a highly sigmoidal dose-response curve, 10 closely resemble those of other lysosomotropic detergents.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, the characteristics of siramesine-induced cell death, e.g., an early lysosome damage occurring prior to cell rounding and death, dependence on cysteine cathepsin activity and cell density as well as a highly sigmoidal dose-response curve, 10 closely resemble those of other lysosomotropic detergents. 36,38 It should, however, be noted that whereas other lysosomotropic detergents have been reported to kill all lysosome-containing cells, 37 siramesine-mediated killing displays selectivity to transformed cells both in vitro and in vivo. 10,18 Our earlier data showing that siramesine induces oxidative stress and that lipophilic but not hydrophilic anti-oxidants effectively inhibit siramesine-induced cell death have suggested that lipid peroxidation may be involved in siramesine-induced lysosomal leakage and cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that damaged entire lysosomes can be autophagocytozed (Stroikin et al 2004;Kiffin et al 2006). Regardless of the mechanism of autophagic sequestration, it does not prevent apoptosis of MSDH-treated cells (Li et al 2000), since the acidic interior of autophagolysosomes is attracting MSDH, which at low pH becomes protonated and acquires properties of a detergent (Firestone et al 1979). …”
Section: Discussionmentioning
confidence: 99%
“…acid phosphatase, β-glucuronidase and cathepsin B, into the cytoplasm (Boyer and Tannock, 1993). Furthermore, Firestone and co-workers proposed a novel approach to target tumour cells by utilizing lysosomal enzymes and synthesized a new class of agents termed lysosomotropic detergents (Firestone et al, 1979). These compounds are designed to be weakly basic so they concentrate within lysosomes as a result of the pH gradient across the lysosomal membrane.…”
Section: Discussionmentioning
confidence: 99%